A new species of Sphaenorhynchus (Anura; Hylidae) from Brazil - Toledo, Luís Felipe [UNESP]; Garcia, Paulo C. A.; Lingnau, Rodrigo; Haddad, Célio F. B. [UNESP] (My University, 2007)
A new species of Sphaenorhynchus, probably closely related to S. surdus, is described from the states of São Paulo, Paraná, and Santa Catarina in the southeast and south of Brazil. This species, Sphaenorhynchus caramaschii sp. nov., is an intermediate species in size within the genus and is characterized by the absence of external tympanum, by the snout from truncate to slightly mucronate in dorsal view and protruding in lateral view, by the presence of a dark line from the snout to the eye, and mainly by differences in the advertisement call (a long call with several notes). It is found in open areas, calling during the wet season of the year, generally, in the deepest area of permanent ponds. Illustrations of the adults, descriptions of the advertisement calls, and a map of geographic distribution of the species are provided. Also, we provide data on the distribution and natural history of S. surdus and describe its advertisement call. Copyright © 2007 Magnolia Press.
Keywords: Amphibia; Atlantic forest; Species description; Sphaenorhynchus caramaschii sp. nov.; Sphaenorhynchus surdus; Anura; Hylidae; Sphaenorhynchus